English Final Semester Assessment at Vocational High School in Semarang - Muhammad Rizky; Laily Nur Affini; Festi Himatu Karima (Journal of English Language Learning, 2023)
aims to find out the supporting factors of students’ English achievements in passing the final semester examination and the teachers’ perspective about obstacles that impact the incompleteness of students learning goals. This research is qualitative, it was carried out at SMK Negeri 4 Semarang, Indonesia. Since English is an international language so, people need to be able to speak English. The data collection method in this study is cluster random sampling, and the researcher chose two classes at the vocational school. They are XI Animation and XI Electronics Engineering. The data was obtained from an interview with the teacher from both classes and the final semester examination score that belongs to the students. The result is the average scores from both of the classes is almost the same, although the two classes have different learning styles, classroom environment, teachers, and different learning method.